(untitled) (Research, Society and Development, 2020)
Studies regarding food management applied to the creation of turtles in an intensive system are still few, triggering an information gap that optimizes the feeding strategies in the different phases and breeding system. It aimed to evaluate the productive management of the jurará (Kinosternon scorpioides) breeding, submitted to different rates (0.5% and 0.6% PV) and feeding frequencies (3 and 5 times / week) during drought and rainy season. Morphometric measurements, individual weight (PI), specific growth rate (TBI), apparent feed conversion (CAA) and growth efficiency (EC) were determined. The data obtained were submitted to analysis of variance (ANOVA) with comparison of means by the Tukey test (p <0.05). In food management, the averages of TBI, CAA and EC were between 0.07 to 10.44; from 0.01 to 0.29; and 0.08 to 1.16, respectively. In conclusion, the animals expressed the highest performance in the dry season with a rate of 0.6% PV and fed 3 times / week and in the rainy season the rate of 0.5% PV being fed 5 times / week.